Malaysia : Financial Sector Assessment Program Financial Sector Performance, Vulnerabilities and Derivatives-Technical Note. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
This Technical Note focuses on financial sector performance, vulnerabilities, and derivatives in Malaysia. The note highlights that banking sector has undergone consolidation while competition has increased following measures implemented under the Financial Sector Master Plan 2001-2010. Malaysian banks are presently well capitalized with comfortable Tier 1 capital ratios. Stronger financial positions and risk management capability have enabled domestic banking groups to pursue overseas expansions, mostly within the region. The importance to some banks of overseas assets and earnings is reaching levels which, based on international experience, warrant a review of internal controls.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet